A Bibliometric Analysis Of The Fragmented Nexus Between Pedagogical Competence, Mindfulness, And Teacher Burnout (2015–2025) - Nur Iffah Qoyyumillah; Imam Nur Aziz; Nashrullah (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2026)
Teacher burnout has escalated from an occupational hazard to a systemic crisis globally, threatening educational sustainability in the post-pandemic era. While pedagogical competence and mindfulness are widely recognized as vital protective factors, (Gap) existing literature remains fragmented, often treating technical teaching skills and psychological well-being as isolated domains rather than synergistic mechanisms. This study aims to map the intellectual structure and thematic evolution of global research connecting teachers' pedagogical competence, mindfulness, and burnout prevention. Employing a bibliometric approach, metadata from Scopus-indexed articles published between 2015 and 2025 were analyzed using VOSviewer to visualize publication trends, co-authorship networks, and keyword co-occurrences. The results reveal a